2008
DOI: 10.1186/1471-2334-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of haemolytic uraemic syndrome in Norway caused by stx 2-positive Escherichia coliO103:H25 traced to cured mutton sausages

Abstract: Background: On 20-21 February 2006, six cases of diarrhoea-associated haemolytic uraemic syndrome (HUS) were reported by paediatricians to the Norwegian Institute of Public Health. We initiated an investigation to identify the etiologic agent and determine the source of the outbreak in order to implement control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 39 publications
3
112
0
1
Order By: Relevance
“…Strains MF2522 and MF2494 had very similar features, including identical ITS sequencing data, ribotype and FT-IR spectra. Both O103:H25 strains were, among other isolates, linked to the Norwegian outbreak in 2006 and show identical multipleloci variable-number tandem-repeat analysis genotypes (Lindstedt et al, 2007;Schimmer et al, 2008). As expected, Figure 4.…”
Section: Polyphasic Analysis and Integration Of Resultssupporting
confidence: 51%
“…Strains MF2522 and MF2494 had very similar features, including identical ITS sequencing data, ribotype and FT-IR spectra. Both O103:H25 strains were, among other isolates, linked to the Norwegian outbreak in 2006 and show identical multipleloci variable-number tandem-repeat analysis genotypes (Lindstedt et al, 2007;Schimmer et al, 2008). As expected, Figure 4.…”
Section: Polyphasic Analysis and Integration Of Resultssupporting
confidence: 51%
“…Although cattle are considered to be the most important source of human infections caused by VTEC O157, they have also been isolated from the intestinal contents of sheep and goats. Food of small ruminant origin has been reported as a source for human VTEC infections (Kosmider et al, 2010;Schimmer et al, 2008;Werber et al, 2007). Transmission occurs through consumption of undercooked meat, unpasteurised dairy products, or water and vegetables contaminated by faeces of carriers.…”
Section: Severity Of Diseasementioning
confidence: 99%
“…Consumption of dry cured sausages made with sheep meat was identified as the cause of an outbreak of VTEC O103:H25 infection in humans (Schimmer et al, 2008;Sekse et al, 2009). In the latter study, bacteria with the same properties, including identical DNA profiles, were found in five dry cured sausage products and sheep meat used as raw material in sausage production and were identical to the isolates from patients.…”
Section: Severity Of Diseasementioning
confidence: 99%
“…The correlation between HUS and EHEC O157 infection has been widely reported and has supported the conclusion that EHEC is a causative pathogen (2)(3)(4)(5). Conversely, HUS has less frequently been reported in outbreaks caused by non-O157 EHEC (i.e., EHEC O104) (6)(7)(8). On the other hand, HUS patients without EHEC isolates have frequently been described (3,4,9,10).…”
mentioning
confidence: 99%